Flipped Classroom: Can It Optimize Students’ Ability to Find Out Main Ideas in Listening Comprehension? - Hesti Rokhaniyah (Lectura : Jurnal Pendidikan, 2017)
The present study attempts to describe whether or not and to what extent FlippedClassroom can optimize the college students’ ability to find out the main idea inlistening, and identify the class climate when Flipped Classroom is implemented. Thedata were derived using several techniques including interview, observation, document,and test. The qualitative data were analyzed using Constant Comparative Method; thequantitative data were obtained by finding out the mean score of two raters. The findingof the research showed that the implementation of Flipped Classroom optimized: (1)students’ ability to find out the main idea including: (a) finding out appropiate topic; (b)describing the location of main idea;(c)providing the meaningful supporting sentences.The enhancement of the students’ scores could be proved that the mean score of pre-testwas 65.1; post-test 1 was 72.5; and post-test 2 was 81.1. Twenty two students from 29students had fulfilled the criteria of passing grade which was 75 in post test 2; and (2)enhanced class climate including: (a) the students were involved actively to previewvideo before class; (b) the students liked to discuss the meaning of target language; (c)most students were encouraged to work with their classmates due to mutual project.Considering inspiring result of this research, it is recommended that English lecturersare able to use this research for: guiding the students to explore their ability to find outthe main idea through Flipped Classroom; and being creative to make class climateinteresting by implementing Flipped Classroom.